Hak-hak Perempuan dalam Surah Al-Nisā’/ 4: 1-4 Perspektif Tafsir Al-Ibriiz - Muhammad Fadli; Nana Gustianda; Aulya Adhli (PT. Willy Print Art, 2025)
The problem that is discussed in this study is, how the Qur'an explains the rights and obligations of women in the Right of Dowry and inheritance for them, then how the interpretation of the al-Ibriiz interpretation of these verses, and how the similarities and differences with other interpretations. The methodology used in this study includes the type of descriptive qualitative research, because the purpose of this study is to collect data on women's rights in the Qur'an using the Library Research method. In the process of searching for reference sources, the author looks for reading sources in the form of books, both interpretation books and other related textbooks, in the form of related scientific documents using research and other library sources. This type of qualitative research uses an analytical narrative method as a method to describe or present facts and facts in the research area. In Library Research, using sophisticated historical methods for women's rights to understand the meaning, which then becomes the focus of research using Islamic feminist analysis. The data is in accordance with the data from the level of understanding of the researcher.